Performance Evaluation of Hotels Affiliated to Shiraz Municipality in order to Promote Tourism Industry - Morteza Shafiee; Milad Fakhr (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2019)
An assessment of the performance of organizations is a process through which useful information can be provided on the success rate of services. In this research, the performance of Shiraz hotels in the tourism industry has been evaluated using mathematical models, their service quality has been measured, and in the end, ways to improve the performance of Shiraz hotels in the tourism industry have been identified. The Stochastic frontier production function method has been used for analysis. Initially, two Cobb-Douglas and Translog production functions are investigated by examining structural parameters and the importance of accuracy in the correct selection of the function, two functional forms are estimated and, according to the likelihood ratio test, the best production function is selected. Data collection was carried out using panel data provided by the Cultural Heritage and Tourism Organization with criteria such as the length of stay of tourists in hotels and the number of rooms available, to the researcher. It should be noted that the hotels under study are those that operate under the supervision of the municipality's modernization and improvement center or use the financial facilities of the organization. In the end, the results indicate that the municipality of Shiraz can increase its efficiency by increasing the budget of the renovation and improvement organization and the number of hotel rooms. In addition, hoteliers can improve their performance in a more economical and optimal way by filling their technical gaps, such as budget and labor.